Comparison of the Effects of Dill Seed, Grape Seed and Date Extracts on Postpartum Hemorrhage Rates in the Fourth Stage of Labor: A Randomized Clinical Trial - Shayan, Arezoo; Refaei, Mansoureh; Parsapour, Hamideh; Masoumi, Seyedeh Zahra; Ahmadinia, Hassan; MoradKhani, Shirin; Sattari, Mahtab; Hamoun, Minoo (Reviews on Recent Clinical Trials, 2025)
BackgroundPostpartum hemorrhage (PPH) is one of the three leading causes of maternal mortality. Herbal medicine is one of the well-known methods of treatment in the world.ObjectiveThis study was conducted to determine and compare the effect of dates, grape seed and dill seed extracts on the PPH rate in women in the fourth stage of labor.MethodsTwo hundred eligible multiparous women visiting the maternity ward in Hamadan for normal delivery participated in this double-blind parallel-group clinical trial. They were randomly divided into four 50-member groups of experiment (3 groups) and control (1 group). The data were collected using a researcher-made questionnaire. In the experimental groups, in addition to routine care and oxytocin administration, the mothers received a capsule containing 15 mg of dill seeds extract or 20 mg of grape seed extract or 5 g of dates extract immediately after the delivery, and then their hemorrhage rates were measured one and two hours after delivery. The control group received routine care, oxytocin, and placebo. Data were analyzed in SPSS 21.ResultsThe hemorrhage changes in the placebo group were much less than the intervention groups at 1 and 2 hours after delivery, and the four groups had a significant difference in terms of hemorrhage in both hours (p <0.001). The overall difference between the dates extract group and the placebo and grape seed groups was also statistically significant (p <0.05).ConclusionAll three extracts of dates, grape seed and dill seeds, especially dates, can be effective in PPH reduction.Clinical Trial Registration NumberIRCT20120215009014N300.
Keywords: anethum graveolens